(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article discusses the reforms implemented in the field of personnel management in the public civil service of China, the analysis of advanced experiences, information on approaches to effective organization and suggestions on the personnel management in Uzbekistan based on the learned foreign experience.